Intragastric Balloon Improves Steatohepatitis and Fibrosis. Issue 1 (15th January 2021) - Lin, Elissa; Huang, Xiaoyan; Pei, Zhiheng; Gross, Jonathan; Popov, Violeta
ABSTRACT: Obesity is a major risk factor for nonalcoholic steatohepatitis (NASH). Although weight loss has been shown to reverse histologic features of NASH, lifestyle intervention alone is often challenging and unfeasible. In this case report, we discuss the effects of intragastric balloon (IGB) therapy on steatosis, fibrosis, and portal pressures. We also demonstrate that improvement in histologic features persist at least 6 months after IGB removal. Although there are little data thus far to support IGB therapy in the treatment of NASH, our case provides evidence of the potential benefit of IGB on improving metabolic parameters and markers of liver fibrosis.